Copigmented Butterfly Pea Flower Extract (Clitoria ternatea L.) as an Antibacterial Agent against Propionibacterium acnes and Its Formulation in Microneedle Patches - Lilis Tuslinah; Adita Diari Fanisa; Mochamad Fathurohman (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Acne vulgaris is a common skin condition often caused by a bacterial infection with Propionibacterium acnes. The extract of butterfly pea flower (Clitoria ternatea L.) contains anthocyanins and other bioactive compounds that have potential as antibacterial agents. Anthocyanins are unstable to heat and light; thus, copigmentation with 1.2% citric acid was performed to maintain their stability. This study aims to evaluate the antibacterial potential of the copigmented extract and to characterize the hyaluronic acid- based microneedle patch formulation as a transdermal delivery system, including organoleptic tests, mechanical tests, and morphology using Scanning Electron Microscopy (SEM), as well as the antibacterial potential of the formulation. The results showed an extract yield of 55.45% with an anthocyanin content of 2.9668 mg/L (expressed as cyanidin-3-glucoside equivalents in the analytical solution), with an inhibition zone classified as strong (10–20 mm), and ANOVA analysis indicated significant differences among concentrations (p = 0.032). The microneedle patch formulation exhibited needle deformation following a standardized 32 N compression test (from 395 ± 1.67 µm to 291 ± 17.56 µm), but showed antibacterial activity with an inhibition zone of 12.82 ± 0.07 mm, classified as strong, and was significantly different from the negative control (p = 0.032).